PENERAPAN HUKUMAN TA’ZIR DI INDONESIA (Suatu Analisis Terhadap Penerapan Hukuman di Lapas Kota Padangsidimpuan) - Hendra Gunawan MA (IAIN Padangsidimpuan, 2018)
This study aims to reveal the application of ta'zir punishment in Indonesia by analyzing the application of punishment in Padangsidimpuan class II B prison, this research is a type of field research with a qualitative approach to comparative analysis. While the data collection in this study was carried out through observation and interview techniques, while data analysis techniques used a comparative model.The results of the analysis show that in prison class II B Padangsidimpuan there are three types of crimes which are crimes of ta'zir or new types of crimes that have not been clearly stated in the Koran regarding the punishment of narcotics, corruption, and punishment for child offenders . Where all the perpetrators were sentenced to ta'zir or punishment based on a judge's decision, from the practice of applying punishment in class II B prison Padangsidimpuan shows that indirectly the terminology of ta'zir punishment in the Islamic criminal law realm has actually been applied in Indonesia, namely correctional institutions